2016
DOI: 10.1007/s11113-016-9393-1
|View full text |Cite
|
Sign up to set email alerts
|

What Will You Do If I Say ‘I Do’?: The Effect of the Sex Ratio on Time Use within Taiwanese Married Couples

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In addition, some studies suggested the sex ratio as a vital factor to assess the empowerment of women in the marriage market [51]. Since the 1980s, the sex ratio at birth in China has become unbalanced, and the implementation of the one-child policy made this problem increasingly complicated.…”
Section: Region-varying Factorsmentioning
confidence: 99%
“…In addition, some studies suggested the sex ratio as a vital factor to assess the empowerment of women in the marriage market [51]. Since the 1980s, the sex ratio at birth in China has become unbalanced, and the implementation of the one-child policy made this problem increasingly complicated.…”
Section: Region-varying Factorsmentioning
confidence: 99%
“…As for sex ratio effects on leisure, another prediction of Becker, they were recently tested in Taiwan by Chang et al (2016). They defined total work time as employment, commuting, and housework.…”
Section: Evidence On Sex Ratio Effectsmentioning
confidence: 99%
“…Our findings also contribute to the literature on sex ratio imbalance in China. Most studies focus on the consequences of the sex ratio imbalance, such as its effects on saving (Du & Wei, 2013; Wei & Zhang, 2011b; Wei et al., 2017); entrepreneurship (Chang & Zhang, 2015; Wei & Zhang, 2011a); real exchange rate (Du & Wei, 2016); crime (Edlund et al., 2013); hypergamy (Du et al., 2014) and intrahousehold allocation (Chang et al., 2016; Du et al., 2014; Edlund et al., 2013; Porter, 2016, 2017). Particularly relevant to this study is Wei et al.…”
Section: Introductionmentioning
confidence: 99%